Ecclesiastical History, Volume II, Books IV-V. Lives of the Abbots. Letter to Egbert. (Loeb Classical Library No. 248) ( PDF, 29.7 MB ) - WeLib
with an English translation by J. E. King, M.A., D. Litt., in two volumes; II, Ecclesiastical History of the English Nation, based on the version of Thomas Stapleton, 1565, books IV and V; Lives of the Abbots; Letter to Egbert Historical works by Bede (672 or 673-735 CE) include his Ecclesiastical History of the English Natio Harvard University Press ; William Heinemann Ltd